INTERVENSI NETIZEN DALAM PROSES DAN PENEGAKAN HUKUM DI INDONESIA - Firman Akbar; Ali Rizky; Kamaruddin (Journal Publicuho, 2024)
The influence of public opinion and "trial by social media" on the law enforcement process in Indonesia using a normative and empirical approach. The introduction explains the background to the importance of understanding the impact of social media on the law. Research methods involve statutory studies, legal cases, and literature studies, as well as collecting primary data through interviews and focus group discussions. This research found that netizen intervention had a positive influence, such as increasing community participation, empowering information, and promoting justice. However, negative challenges and impacts are also significant, including the spread of misinformation, political and legal discrimination, and the manipulation of personal interests. Furthermore, "trial by social media" affects legal independence through increased public pressure, influence on public perception, dissemination of inaccurate information, decreased public trust, manipulation by certain groups, and obstruction of effective legal processes.